Strategi pengembangan lingkungan bandara sehat di Bandara Internasional Sultan Syarif Kasim II Pekanbaru Provinsi Riau - Fazli Fazli; Sukendi Sukendi (Pelantar Press, 2022)
Healthy airport is an airport environmental condition that is clean, safe, comfortable and healthy for the working community and the airport community in carrying out their activities. The goal of healthy airport is to create a healthy airport environment that does not pose a risk to public health and to create a clean, safe, comfortable and healthy airport environment for the airport community in carrying out its activities. To achieve this condition, it is necessary to develop a strategy to develop a healthy airport environment. One of the international airports belonging to the Pekanbaru city government that needs to develop a healthy airport environment is the Sultan Syarif Kasim II International Airport, Pekanbaru. The purpose of this research is to analyze the environmental conditions of a healthy airport, to analyze the components that play a role in the development of a healthy airport environment and to develop a strategy for development of a healthy airport environment at Sultan Syarif Kasim II International Airport, Pekanbaru. The method used was interviews, observvation and documentation. To data analysis used SWOT. The strategy for developing a healthy airport environment is to take advantage of good airport environmental conditions and is supported by adequate facilities and infastructure to increase community satisfaction, so as to attract public interest (investors) to use airport services through the support of vertical agencies or the Riau Provincial Government in the form of budget assistance for development of a healthy airport environment and utilizing quality human resources owned by the airport to plan good activities for the fulfillment of the increased budget in the development of a healthy airport environment carried out by the airport through the Healthy Airport Forum that has been established, as well as collaborating (MoU) with third parties in the management of waste and B3 waste which are bound by regulations and SOP’s in force at the airport.